Nutrient Management Approaches in Pigeonpea [Cajanus Cajan (L.) Millsp.] Cultivation in Acid Soils of North East Hill Regions-A Review (SAARC Journal of Agriculture, 2025)
Nutrient management is a strategy that aims to optimize the soil fertility and plant nutrient supply to achieve desired crop productivity. This may be achieved by maximizing the benefits derived from all available plant nutrient sources in an integrated manner. Nutrient management involves balanced utilization of fertilizers, organic substances, and biological sources of plant nutrients to maintain or enhance soil productivity. Sustainable agricultural production along with conservation of soil fertility may be attained by cautious use of integrated nutrient management strategies involving the reasonable use of both inorganic and organic nutrient sources. The comprehensive use of both chemical and organic fertilizers in relation to the yield and yield components is of utmost importance for ensuring food security. Pigeonpea cultivation systems include several types of organic resources, including farmyard manure, vermicompost, animal manure, green manure, crop residue, compost and industrial waste.SAARC J. Agric., 23(1):68-81 (2025)